Image of Confucius Institute in Italian Media Discourse - Volpe, Marco; Qiuyang, Li (Sinología hispánica. China Studies Review, 2016)
Along with a considerable increase of the people involved in studying Chinese culture and Chinese language, Confucius Institute, initially founded in 2004 in Seoul, South Korea, provoked different reactions regarding to the management and the activity held. Especially on American press, the debate focused on what the real aim of the project consists in, has been retained responsible for political propaganda and a threat for the academic freedom. Soon the debate involved reporters, journalists, Chinese Studies experts, sinologists and Confucius Institutes directors from every part of the world, leading the debate to an international dimension. 32 articles published since 2010 on the Italian national newspapers, periodicals, specialized website and online channels, have been collected and examined in order to propose a critical analysis on how the image of Confucius Institute is perceived in Italy through examining the discourse of the Italian press and the voices of the experts in the press.